Providing a framework for knowledge sharing in knowledge-based organizations according to social capital indicators - Saeed Ghorbani; Shayan Naghdi Khanachah (Annals of Management and Organization Research)
Purpose: This study aimed to provide a framework for examining knowledge sharing from the perspective of social capital in knowledge-based organizations. For this purpose, the social capital and knowledge sharing literature has been reviewed and appropriate dimensions and components have been selected for use in the proposed framework. Research methodology: The number of experts participating in this study was 12. Kendall’s W Ranks is a statistical index for assessing the degree of agreement in a group. This statistical index, which is related to non-parametric statistics, is used to assess the degree to which a number of evaluators agree on the ranking of several factors. Result: This research's proposed framework shows that the main bottleneck in the knowledge sharing process is the sender. Numerous factors affect the motivation, quantity and quality of knowledge shared by him. The proposed conceptual model shows the factors in the field of social capital well. This means that the organization's managers should pay special attention to people with knowledge to activate the process of knowledge sharing in the organization as a driving force. Limitations: This research only described knowledge-based organizations. Contribution: The proposed conceptual framework makes a good distinction between formal and informal knowledge-sharing channels in a knowledge-based organization. Formal channels are controlled and manageable channels. Although the main burden of knowledge sharing in organizations lies with informal channels, the more managers can shift the organization's knowledge to formal channels, the more they can manage the process. This is a part of the job that social capital, in particular, helps to achieve. The proposed framework discusses the acceptance of the use of formal frameworks. Keywords: Social capital, Knowledge management, Knowledge sharing, Expertise method